Orexins activates protein kinase C-mediated Ca(2+) signaling in isolated rat primary sensory neurons - Ozcan, M; Ayar, A; Serhatlioglu, I; Alcin, E; Sahin, Z; Kelestimur, H (Physiological research, 2010)
Previous results have suggested that orexins causes a rise of intracellular free calcium ([Ca(2+)](i)) in cultured rat dorsal root ganglion (DRG) neurons, implicating a role in nociception, but the underlying mechanism is unknown. Hence, the aim of the present study was to investigate whether the orexins-mediated signaling involves the PKC pathways in these sensory neurons. Cultured DRG neurons were loaded with 1 micromol Fura-2 AM and [Ca(2+)](i) responses were quantified by the changes in 340/380 ratio using fluorescence imaging system. The orexin-1 receptor antagonist SB-334867-A (1 microM) inhibited the calcium responses to orexin-A and orexin-B (59.1+/-5.1 % vs. 200 nM orexin-A, n=8, and 67+/-3.8 % vs. 200 nM orexin-B, n=12, respectively). The PKC inhibitor chelerythrine (10 and 100 microM) significantly decreased the orexin-A (200 nM)-induced [Ca(2+)](i) increase (59.4+/-4.8 % P<0.01, n=10 and 4.9+/-1.6 %, P<0.01, n=9) versus response to orexin-A). It was also found that chelerythrine dose-dependently inhibited the [Ca(2+)](i) response to 200 nM orexin-B. In conclusion, our results suggest that orexins activate intracellular calcium signaling in cultured rat sensory neurons through PKC-dependent pathway, which may have important implications for nociceptive modulation and pain.
Keywords: bolest; Benzoxazoles; Pain; benzoxazoly; Neuropeptides; orexiny; neurotransmiterové látky; Urea; intracelulární signální peptidy a proteiny; Neurotransmitter Agents; Orexins; krysa rodu Rattus; spinální ganglia; nociceptory; zvířata; Calcium Signaling; Cells, Cultured; Nociceptors; potkani Wistar; neuropeptidy; nervové receptory; Naphthyridines; Intracellular Signaling Peptides and Proteins; močovina; Rats, Wistar; kultivované buňky; vápníková signalizace; Protein Kinase C; Rats; proteinkinasa C; Animals; Sensory Receptor Cells; Ganglia, Spinal; naftyridiny